Effectiveness of hepatitis B hyperimmunglobulin and vaccine in preventing perinatal transmission in children born from a mother with chronic B hepatitis - Feyza Gökben Kahveci; Hasret Ayyildiz Civan; Özgül Salihoğlu (Zaslavsky O.Yu., 2021)
Background. Viral hepatitis is still one of the important health problems all over the world today. Hepatitis B is a life-threatening liver infection that can cause chronic infections. It increases the risk of death from cirrhosis and hepatocellular carcinoma. One of the most important factors in chronic or acute hepatitis B infection is the age of infection. The earlier the virus is encountered, the greater the risk of chronicity of the disease. Prevention of perinatal transmission of the disease is of great importance. The most effective way to control hepatitis B infection is to prevent contamination and ensure immunity. There is a safe and effective vaccine available that provides 98-100% protection against hepatitis B. Prevention of hepatitis B infection control the development of complications, including chronic disease and liver cancer. The purpose of this study is to evaluate the efficacy of the vaccine and hepatitis immunoglobulin administered to prevent perinatal hepatitis B infection transmission in babies born to mothers with chronic hepatitis B infection. Materials and methods. Fifty-five children born to mothers with chronic hepatitis B infection in our hospital between January 1, 2013 and January 1, 2019 and accepted to participate in the study were included in our study. In retrospective file examination, maternal gestational age, maternal hepatitis B test, delivery method, baby birth weight, baby birth week, whether immunoglobulin and hepatitis B vaccine were administered to these babies in the first 24 hours after birth, hepatitis B vaccine and immunoglobulin administration time, bathroom status, infant hepatitis B tests, additional studies on the child's viral diseases (hepatitis C, human immunodeficiency virus) and the baby's liver transaminase tests (aspartate aminotransferase, alanine aminotransferase) were evaluated. The vaccination program of the baby, the control of the mother's hepatitis B status, the time of the breast milk intake, the height and weight of the baby, the follow-up of the mother during pregnancy and the drug use status were collected. Children previously diagnosed with chronic B hepatitis were excluded from the study. Results. Hepatitis B surface antigen tests were positive in two infants who received three doses of hepatitis B vaccine. The mothers of both of these babies were positive for hepatitis B surface antigen and hepatitis B envelope antigen. Forty-three (78.2 %) patients had a protective antibodies to hepatitis B surface antigen, while 12 (21.8 %) didn't have it. Conclusions. Hepatitis B serology should be checked in women who live in countries with high risk of chronic hepatitis B infection and who are pregnant, and babies born to these mothers should have hepatitis B vaccine and immunoglobulin.